Customer Switching Patterns in Competitive and Noncompetitive Service Industries - Roos, Inger; Edvardsson, Bo; Gustafsson, Anders (Journal of service research : JSR, 2004)
This article is about behavioral change in customer relationships. Changes in customer switching behavior are compared in five different service industries. Switching barriers and the competitive industrial situations in the comparison between industries also revealed changes in behavior in an industrial monopoly in which switching to alternative external service providers was not an option. This kind of switching was articulated as internal switching. The behavioral change was therefore assessed in terms not only of frequency but also of type of change. The switching ability to cause change, called configuration energy, even caused a change in behavior at the highest level in a noncompetitive industry in which there was a lack of switching alternatives. Total change was considered to be a result of the higher energy level driving the switching configuration than when the change was partial.